Malaysian reference network modelling for photovoltaic impact study - Annathurai, Vinodh (2017)
The burning of abundant fossil fuel amount to accommodate the energy demand causes emission of the greenhouse gas (GHG) which is contribute to the climate change. The Distributed Generation (DG) and renewable energy resources is one promising approach to reduce the emission, thereby mitigating climate change. However, most of the DG and renewable energy resources, especially the photovoltaic (PV) system is intermittent and often fluctuates. In this regard, this thesis focuses on the analysing the impact of PV integration at the medium voltage (MV) network. More precisely, the network losses and voltage issues are used to evaluate the effects of four variables; PV system installed locations, PV variability index (VI), different time resolution of PV generation profiles used and the PV penetration levels. The Malaysian Reference Network (RN) is modelled with the intention to analyse the impact of PV integration at the Medium Voltage (MV) network. Moreover, the breakdown of network losses for the Malaysian MV network is quantified by utilising the RN models. All case studies have been carried out for the urban, semi-urban and rural MV networks. The findings suggest that PV system installed at the end of the 11kV feeder for the rural and semi-urban produces significant network losses reduction than urban networks, which is driven by feeder length and load size. The findings also show that different categories of VI produce different impact on the networks. Voltage fluctuation and voltage step change are the two main concerns of various PV variability on the MV network. In addition, the different time resolution of real solar PV generation profile was collected to be used in the case study. By analysing different ranges of time resolution, it is suggested that a 15-minute time resolution PV generation profiles data are sufficient in network assessment study with approximately 5% error. The use of hourly PV generation data will cause up to 31% loss of accuracy. Furthermore, a case study was done to evaluate the impact of different PV penetration levels. The results show that PV integration above 60% and 100% penetration level will likely cause voltage rise violation in rural and urban networks, respectively. The research also suggests that the maximum PV penetration levels for a MV Malaysian network are based on several network performance indicators. In conclusion, the results show that location of PV system, PV variability, time resolution and PV penetration level are the key parameters to study the impact of PV in the MV networks.